How to effectively use interactivity to improve visual analysis and communication in groups of novices or experts - Viana, Maria do Mar Guiod de Castro Couto (2020)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence